Performance-Based Seismic Design of Steel Frames Utilizing Colliding Bodies Algorithm - H. Veladi (The Scientific World Journal)
A pushover analysis method based on semirigid connection concept is developed and the colliding bodies optimization algorithm is employed to find optimum seismic design of frame structures. Two numerical examples from the literature are studied. The results of the new algorithm are compared to the conventional design methods to show the power or weakness of the algorithm.